2009
DOI: 10.1089/pho.2007.2163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dentin Hardness on Ablation Rate with Er:YAG Laser

Abstract: Objective: This study used artificially demineralized bovine dentin to ascertain the effect of hardness of demineralized dentin on ablation rate with the Er:YAG laser. Background Data: Before restoration of carious teeth, it is necessary to ablate any infected dentin that cannot be remineralized due to softening by the invading caries. A correlation has been suggested between the ablation efficiency of the Er:YAG laser and the progression of caries in dentin. To the best of our knowledge, no studies have inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Although previous studies [29][30][31] have attempted to determine Er:YAG laser parameters for carious dentin, the literature is scarce and inconclusive about this. Katleen et al 32 claimed that energy output £ 200 mJ should be applied using the Er:YAG laser for caries-affected dentin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies [29][30][31] have attempted to determine Er:YAG laser parameters for carious dentin, the literature is scarce and inconclusive about this. Katleen et al 32 claimed that energy output £ 200 mJ should be applied using the Er:YAG laser for caries-affected dentin.…”
Section: Discussionmentioning
confidence: 99%
“…This also confirms the findings of previous investigations that similar effects of laser parameters were also demonstrated. 29,33 The selected pulse frequency has been also considered the most influential parameter during dentin ablation. 34 Previous studies by Raucci-Neto 35,36 showed that the increase of Er:YAG laser frequency provided greater dentin caries removal, in which a larger amount of tissue was removed during irradiation of demineralized substrate, creating a deeper cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The carious dentin has more water content than sound dentin, and this variation between the both substrates was significant enough to affect the gross amount of tissue removed. The relation between the water content of the substrate and the ablation rate was previously observed by Armengol et al (1999), Hibst and Keller (1989), Mercer et al (2003), as well as the higher ablation of demineralized dental tissue (Osuka et al, 2009).…”
Section: Discussionmentioning
confidence: 54%